The Use of Videos to Improve Low Achieving Students' Understanding of Mathematics - Tika Dwi Pamungkas; Yuli Rahmawati; Uwes Anis Chaeruman (Jurnal Basicedu, 2022)
The question of how to improve the learning of students who score low in mathematics poses a significant challenge for researchers and teachers. Researchers investigated whether the use of video could help low-achieving students. To achieve this goal, this research uses a qualitative approach. Data was collected through interviews, pre-test, and post-test. This study involved 15 students from 3 different classes and two mathematics teachers. The researcher interviewed students and teachers about their first impressions using videos and gave a pre-test and post-test to check the answers' sentences. This study indicates that video makes it easier for students to remember the material, and students can influence what affects their understanding of mathematical concepts. The use of video proved to be an effective strategy in increasing the knowledge of mathematical concepts of low achieving students.